A Ratiometric Fluorescent Probe for Hypochlorite and Lipid Droplets to Monitor Oxidative Stress - Mousumi Baruah; Anal Jana; Niharika Pareek; Shikha Singh; Animesh Samanta (Biosensors, 2023)
Mitochondria are valuable subcellular organelles and play crucial roles in redox signaling in living cells. Substantial evidence proved that mitochondria are one of the critical sources of reactive oxygen species (ROS), and overproduction of ROS accompanies redox imbalance and cell immunity. Among ROS, hydrogen peroxide (H2O2) is the foremost redox regulator, which reacts with chloride ions in the presence of myeloperoxidase (MPO) to generate another biogenic redox molecule, hypochlorous acid (HOCl). These highly reactive ROS are the primary cause of damage to DNA (deoxyribonucleic acid), RNA (ribonucleic acid), and proteins, leading to various neuronal diseases and cell death. Cellular damage, related cell death, and oxidative stress are also associated with lysosomes which act as recycling units in the cytoplasm. Hence, simultaneous monitoring of multiple organelles using simple molecular probes is an exciting area of research that is yet to be explored. Significant evidence also suggests that oxidative stress induces the accumulation of lipid droplets in cells. Hence, monitoring redox biomolecules in mitochondria and lipid droplets in cells may give a new insight into cell damage, leading to cell death and related disease progressions. Herein, we developed simple hemicyanine-based small molecular probes with a boronic acid trigger. A fluorescent probe AB that could efficiently detect mitochondrial ROS, especially HOCl, and viscosity simultaneously. When the AB probe released phenylboronic acid after reacting with ROS, the product AB–OH exhibited ratiometric emissions depending on excitation. This AB–OH nicely translocates to lysosomes and efficiently monitors the lysosomal lipid droplets. Photoluminescence and confocal fluorescence imaging analysis suggest that AB and corresponding AB–OH molecules are potential chemical probes for studying oxidative stress.